2002
DOI: 10.1287/orsc.13.1.36.539
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Acquisition Performance: The Role of Transfer Effects

Abstract: Drawing on work from transfer theory at the individual unit of analysis, this study examines positive and negative transfer effects in organization acquisitions. Data from 96 organizations reveal that, consistent with theories on positive transfer of industry knowledge, similar acquisitions are positively related to acquisition performance. In addition, consistent with theory on negative transfer of past acquisition knowledge, second acquisitions underperform first acquisitions, particularly when first and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(271 citation statements)
references
References 39 publications
10
254
1
6
Order By: Relevance
“…Yelle 1979). However, diverse empirical research studies have shown that the principle of learning-curve theory cannot be transferred one-to-one to complex strategic management settings (Ellis et al 2011;Finkelstein and Haleblian 2002;Haleblian and Finkelstein 1999;Hayward 2002;Zollo 2009; see Barkema and Schijven 2008b for an overview of research on organizational learning in acquisition settings). The results of prior empirical studies show evidence that in strategic management settings, as against manufacturing settings, learning relates to the quality rather than to the quantity of experience (Hayward 2002).…”
Section: Transfer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yelle 1979). However, diverse empirical research studies have shown that the principle of learning-curve theory cannot be transferred one-to-one to complex strategic management settings (Ellis et al 2011;Finkelstein and Haleblian 2002;Haleblian and Finkelstein 1999;Hayward 2002;Zollo 2009; see Barkema and Schijven 2008b for an overview of research on organizational learning in acquisition settings). The results of prior empirical studies show evidence that in strategic management settings, as against manufacturing settings, learning relates to the quality rather than to the quantity of experience (Hayward 2002).…”
Section: Transfer Effectsmentioning
confidence: 99%
“…Prior empirical studies analyzing the performance effects of serial acquisitions generally pursue two variant key topics: the effect of time or more specifically acquisition patterns (Klarner and Raisch 2013;Laamanen and Keil 2008;Prescott 2011, 2012;see Shi et al 2012 for an overview) and the role of experience on learning effects (Ellis et al 2011;Finkelstein and Haleblian 2002;Haleblian and Finkelstein 1999;Hayward 2002;Meschi and Métais 2013;Vermeulen and Barkema 2001; see Barkema and Schijven 2008b for an overview). We interconnect these two perspectives by introducing the concept of strategic consistency, which we define in this paper as the coherence of strategic directions of acquisitions within a series.…”
Section: Introductionmentioning
confidence: 99%
“…Finkelstein and Haleblian (2002) find a positive and significant relationship between acquirer performance and their continuous measure of relatedness.…”
Section: Notesmentioning
confidence: 71%
“…4 The benefits to similarity in this context arise because such dynamic complementarities may be greater if the industries in question share some basic features (March, 1991), or because some common characteristics facilitate their exploitation (Finkelstein & Haleblian, 2002;Prahalad & Bettis, 1985). The degree of dynamic complementarity between industries thus depends on the balance between variety and similarity (Christensen & Foss, 1997).…”
Section: Resource Complementaritymentioning
confidence: 99%
See 1 more Smart Citation